1989
DOI: 10.1084/jem.170.2.449
|View full text |Cite
|
Sign up to set email alerts
|

Protection against streptococcal cell wall-induced arthritis by pretreatment with the 65-kD mycobacterial heat shock protein.

Abstract: Arguments for an involvement of bacteria in the pathogenesis ofchronicjoint inflammation (arthritis) are several (1-12). To study the pathogenetic mechanism ofbacteriuminduced sterile arthritis, different animal models are used, among which, Mycobacterium tuberculosis-induced or adjuvant arthritis (AA)t (2) and streptococcal cell wall (SCW)-induced arthritis (1) are the best known. In both models, bacterium-specific T lymphocytes have been demonstrated to play a crucial role (13-24, and van den Broek, M. F, M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(67 citation statements)
references
References 47 publications
(66 reference statements)
1
66
0
Order By: Relevance
“…On days 3,6, and 9, medium was replaced with medium containing 10% autologous serum, 10 units/ml of recombinant interleukin-2 (rIL-2), and 10 units …”
Section: Methodsmentioning
confidence: 99%
“…On days 3,6, and 9, medium was replaced with medium containing 10% autologous serum, 10 units/ml of recombinant interleukin-2 (rIL-2), and 10 units …”
Section: Methodsmentioning
confidence: 99%
“…In addition, in SNP-pretreated groups, rats that did develop AA were found to have lower clinical as well as radiographical scores compared with rats ofthe FIA-pretreated control groups (Tables 1 and 2). Interestingly, SOP, an A'-acetylated octapeptide lacking the N-terminal threonine of 11,14,17,19,19,21,23 SNP, did not have any protective capacity (experiment 2, Tables 1 and 2), AA incidence and severity in SOP-pretreated rats were not difTerent from FtA-pretreated controls (Tables t and 2), This points to the specificity of the SNP effect in AA, It has been postulated that suppression of autoimmune disease in animals is usually caused by the induction of tolerance to the autoimmune disease-inducing antigen (Higgins & Weiner, 1988;Thomson et al, 1988;Clayton et al, 1989), i,e, the protection against mycobacteria-induced arthritis after pretreatment with whole mycobacteria or the 65-kD HSP, is due to induction of tolerance (Grey & Waksman, 1967;Cozine et al, 1972;van den Broek et al, 1989), This led us to investigate the cellular immune response of the rats to SNP, SOP and M. tuberculosis in vivo and in vitro after 35 days of pretreatment but before induction of AA and also 35 days after induction of AA, Before induction of AA, SNP-pretreated rats showed a DTH to SNP, but not to M. tuberculosis (Table 3), Normal rats and FIA-pretreated rats did not show a DTH to SNP, An in vitro proliferative response of splenic MNC to both SNP and M. tuberculosis is found in SNP-pretreated rats, but not in normal or FtA-pretreated rats (Table 3), Interestingly, no crossreactivities between SOP and SNP or M. tuberculosis were observed (Table 3), This is consistent with the fact that T cell clones A2b and A2c do not recognize the epitope without the N-terminal threonine (van der , Therefore it can be concluded that the threonine at position of 180 ofthe 65-kD mycobacterial HSP is important for immunogenicity of the nonapeptide.…”
Section: Resultsmentioning
confidence: 99%
“…Erythrocytes were eliminated by Ficoll-Paque gradients. Adherent cells were removed by l-h incubation on Petri dishes (Falcon 3003) and by a further l-h incubation with nylon wool (van den Broek et al, 1989). After extensive washing, 5-10 x 10' nylon wool-enriched T cells were transferred intravenously to naive rats.…”
Section: Transfer Of Spleen T Cells To Naive Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protection against adjuvant arthritis in Lewis rats induced by immunization with self hsp60 peptide [52], protection against adjuvant arthritis by vaccination with mycobacterial hsp60 peptide cross reactive to self hsp60 [53] have confirmed the involvement of hsp60 in adjuvant arthritis. Similarly immunization with mycobacterial hsp60 conferred protection against streptococcal cell wall induced arthritis in Lewis rats [54]. The hsp60 also been implicated in rheumatoid arthritis (RA) of humans.…”
Section: Candida Albicans Candidiasis Hsp90mentioning
confidence: 99%